PENGARUH PEMBELAJARAN DAN KOMITMEN PELAKU USAHA TERHADAP KINERJA USAHA YANG DI MODERASI JIWA KEWIRAUSAHAAN PADA INDUSTRI TAHU & TEMPE DI KOTA PEKANBARU - Nur, Fadilalah; Susi, Hendriani; Rosenelly, Roesdi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
This research aims to determine the influence of learning and commitment ofbusiness actors on business performance moderated by the entrepreneurial spiritin the tofu & tempeh industry in Pekanbaru City. The population in this researchis female MSME actors in the tofu & tempe industry in Pekanbaru City, totaling50 business actors. The number of samples in this research was 50 businessactors based on predetermined criteria. The sampling technique in this researchused the Purposive Sampling method. The data analysis method for this researchuses SPSS. The research results show that there is an influence of learning onbusiness performance. The commitment of business actors influences businessperformance. The entrepreneurial spirit is able to moderate the commitment ofbusiness actors which influences business performance. Keywords: Learning, Business Actor Commitment, Business Performance,Entrepreneurial Spirit